A study of the social profile of indigenous people aged 5 to 14 years old in Ecuador: Analyzing and understanding key aspects - Ortega-Auquilla, Diego Patricio; Bonilla-Marchan, Andrés Marcelo; Garcés-Chiriboga, Marcela Verónica; Abad-Calle, Joana Valeria (Dominio de las Ciencias, 2019)
The objective behind this study was to investigate the indigenous people, aged 5 to 14 years old, in Ecuador in order to know about their conditions regarding sociodemographic and socioeconomic statuses and aspects concerning access to technology. It was also examined the implications these conditions may have to access education among indigenous minors, and the activities they perform in society. In order to achieve the objectives of this study, a descriptive analysis and a multidimensional statistical analysis were carried out. Available data from the National Survey of Employment, Unemployment and Underemployment of Ecuador (ENEMDU), conducted by the National Institute of Statistics and Censuses (INEC) in 2016, was utilized as the main source of information. The descriptive analysis showed the frequencies and the percentages of the variables that were explored by this study. The multidimensional statistical analysis was employed with the aim of showing the main and the most important criteria of differentiation and classification in different clusters of people under study. The method employed was the multiple correspondence analysis, which showed the criteria of differentiation and a hierarchical clustering that defined the clusters of people based on their common characteristics.